Developing Tangerang BISA and Tangerang EMAS Programs Based Cash Waqf as Solution for MSMEs Financing in Tangerang City (ZISWAF: Jurnal Zakat dan Wakaf, 2025)
The purpose of this research is to design a model for developing Tangerang BISA and Tangerang EMAS programs based cash waqf as a solution for SMEs financing in Tangerang City. The Government of Tangerang City and Islamic Social Bank or Micro Waqf Bank can collaborate to realize the MSMEs financing in order to improve the welfare in Tangerang City. This study uses a qualitative approach with descriptive analysis method through literature study. Data collection techniques in this study were carried out through secondary data. This study shows that the design of the MSMEs financing development model based on cash waqf can be implemented with a partial scheme and integrated scheme. The government of Tangerang City can cooperate with nadzir institutions to create a Micro Waqf Bank so that this cash waqf-based financing development model can be implemented and bring benefits to the SMEs in Tangerang City. Future researchers are expected to be able to develop assistance mechanisms and contracts in financing based cash waqf